KESESUAIAN DAN DAYA DUKUNG KAWASAN PANTAI RONELA BAGI PENGEMBANGAN EKOWISATA Di DUSUN RUMAH OLAT KECAMATAN SERAM UTARA - Merlin Latutiene; Henderina Lelloltery; M. M.S Putileihalat (Universitas Lambung Mangkurat, 2023)
This study aims to determine the suitability of Ronela Beach Tourism for the Development of Ronela Beach Ecotourism and to analyze the carrying capacity of the Ronela Beach area for Coastal Ecotourism Activities. The method used in this research is survey method with descriptive analysis. To describe in a systematic, factual and accurate manner regarding the suitability and carrying capacity of the Ronela Beach Area for the Development of Coastal Ecotourism in Rumah Olat Hamlet. Data collection techniques used by researchers in this study are interview and observation techniques. The results of the study show that the Ronela beach area is very suitable for beach ecotourism activities with a beach tourism suitability index value of 83.3% including the